Inovasi Penerapan Penilaian Portofolio dalam Mahārah Qirā’ah Mata Pelajaran Bahasa Arab - Purnomo, Hamdan Hadi; Baroroh, R Umi; Arju, Salsabila (Prodi Pendidikan Bahasa Arab FTK UIN Sunan Ampel, 2025)
Purpose- This study aims to explore the innovative application of portfolio assessment in teaching Mahārah Qirā'ah at SDIT Salsabila Al Muthi'in Bantul, in order to improve students' reading skills and identify the benefits and challenges faced during the implication of this assessment. Design/Methodology/Approach- The research used a qualitative method with a case study design. Data are collected through observation, interviews, and document analysis. This approach allowed for a deep dive into the implementation context and direct experience during the portfolio evaluation process in Arabic language learning. Findings- The innovative implementation of portfolio assessment was able to increase students' motivation, engagement, and encourage the development of critical, creative, and reflective thinking skills. Students can demonstrate progress in Arabic reading through structured activities, such as daily journaling, poster making, and story presentations. Clear rubrics help students to understand the teacher expectations and improve the quality of learning. Research Limitation/Implications- This research was limited to analyzing the innovation of the application of the Maharah Qira’ah portfolio in Arabic language subjects at the elementary school level without any field testing. However, this research serves as a reference in portfolio-based assessment in Arabic language learning.